Characterization of CaCO3 microspheres fabricated using distilled water - Javeed Shaikh, Mohammed; Abd Manaf, Ali; Nadiawati, Alias (Malaysian Society of Analytical Sciences, 2016)
Calcium carbonate (CaCO3 ) microspheres (μ-spheres) are widely used as inorganic templates (or cores) for fabricating nanoengineered microcapsules. Deionized water is commonly used in the fabrication of CaCO3 μ-spheres using precipitation reaction between calcium chloride (CaCl2 ) and sodium carbonate (Na2CO3 ) solutions under vigorous stirring. However, in the current work distilled water was used throughout the experiments. Furthermore, two simple fabrication approaches, namely membrane filtration and centrifugation approaches, were used in order to understand the effect of different experimental factors on the size and shape of CaCO3 μ-spheres. For the membrane filtration approach, the experimental factors tested included mixing procedure of solutions, stirring speeds, drying techniques, and types of filter paper used. For the centrifugation approach, the experimental factors tested included mixing procedure of solutions, stirring speeds, centrifugation times, drying techniques, and quantity of washing agents used. The size measurements and shape of the CaCO3 μ-spheres were investigated using compound microscopy. Scanning electron microscopy (SEM) was used to observe the fine surface morphological details of the CaCO3 μ-spheres. Overall results indicate that the centrifugation approach can yield better CaCO3 μ-spheres as compared to the membrane filtration approach in terms of narrow size distribution and uniform spherical shape. The fabricated CaCO3 μ-spheres can be used as inorganic templates for fabricating nano-engineered microcapsules.